Enhanced Recovery in Surgical Intensive Care: A Review - Jovanović, Gordana; Jakovljević, Dea Karaba; Lukić-Šarkanović, Mirka (Frontiers in Medicine, 2018)
Patients are admitted to the surgical intensive care (SICU) unit after emergency and elective surgery. After elective surgery, for further support, or to manage coexisting comorbidities. The implementation of the ERAS (Enhanced recovery after surgery) protocols in surgery should decrease the need for ICU beds, but there will always be unpredicted complications after surgery. These will require individual management. What we can do for our surgical patients in ICU to further enhance their recovery? To promote early enhanced recovery in surgical intensive care—SICU, three areas need to be addressed, sedation, analgesia, and delirium. Tools for measurement and protocols for management in these three areas should be developed to ensure best practice in each SICU. The fourth important area is Nutrition. Preoperative screening and post-operative measurement of the state of nutrition also need to be developed in the SICU. The fifth important area is early mobilization. ERAS protocols encourage early mobilization of the critically ill patients, even if on mechanical ventilation. Early mobilization is possible and should be implemented by special multidisciplinary ICU team. All team members must be familiar with protocols to be able to implement them in their field of expertise. Personal and professional attitudes are critical for implementation. In the core of all our efforts should be the patient and his well-being.